Enterococcus alcedinis sp. nov., isolated from common kingfisher (Alcedo atthis) - Frolková, Petra; Švec, Pavel; Sedláček, Ivo; Mašlaňová, Ivana; Černohlávková, Jitka; Ghosh, Anuradha; Žůrek, Luděk; Radiměřský, Tomáš; Literák, Ivan (International journal of systematic and evolutionary microbiology, 2013)
Two Gram-positive, catalase-negative bacterial strains were isolated from the cloaca of common kingfishers (Alcedo atthis). Repetitive sequence-based PCR fingerprinting using the (GTG)5 primer grouped these isolates into a single cluster separated from all known enterococcal species. The two strains revealed identical 16S rRNA gene sequences placing them within the genus Enterococcus with Enterococcus aquimarinus LMG 16607(T) as the closest relative (97.14 % similarity). Further taxonomic investigation using sequencing of the genes for the superoxide dismutase (sodA), phenylalanyl-tRNA synthase alpha subunit (pheS) and the RNA polymerase alpha subunit (rpoA) as well as application of whole-cell protein fingerprinting, automated ribotyping and extensive phenotyping confirmed that both strains belong to the same species. Based on data from this polyphasic study, these strains represent a novel species of the genus Enterococcus, for which the name Enterococcus alcedinis sp. nov. is proposed. The type strain is L34(T) (= CCM 8433(T) = LMG 27164(T)).
Keywords: Animals; Enterococcus; Birds; Superoxide Dismutase; superoxiddismutasa; DNA bakterií; Phenylalanine-tRNA Ligase; bakteriální geny; RNA, Ribosomal, 16S; peptidové mapování; DNA, Bacterial; Molecular Sequence Data; Peptide Mapping; zastoupení bazí; ptáci; Phylogeny; molekulární sekvence - údaje; Czech Republic; DNA-Directed RNA Polymerases; Base Composition; Bacterial Typing Techniques; DNA řízené RNA-polymerasy; Sequence Analysis, DNA; ribotypizace; techniky typizace bakterií; Česká republika; Genes, Bacterial; zvířata; fenylalanin-tRNA-ligasa; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S; Ribotyping